1994
DOI: 10.1007/bf00173019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of desipramine-induced blockade of neuronal uptake mechanisms on adrenoceptor-mediated responses in the guinea-pig colon

Abstract: In order to clarify whether adrenoceptors in the guinea-pig distal colon are under sympathetic control, we assessed possible variations in the sensitivity to adrenoceptor agonists after blockade of neuronal catecholamine uptake mechanisms by desipramine (DMI). First, experiments were carried out to investigate the effects of DMI added in the organ bath on propulsion velocity, endogenous and [3H] prelabelled acetylcholine overflow, electrically evoked noradrenaline overflow and longitudinal smooth muscle tone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Opiate antagonism with naloxone did not affect it. These results suggested that a neuronal factor involving cholinergic transmission but not the opiate receptor might be partly related to the regulation of basal tone, because both tetrodotoxin and clonidine, but not naloxone, were reported to inhibit resting endogenous acetylcholine overflow in the guinea-pig colon (Marino et al 1994). These antagonists and agonists had no effects on the basal tone of the duodenum, jejunum, ileum and rectum (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…Opiate antagonism with naloxone did not affect it. These results suggested that a neuronal factor involving cholinergic transmission but not the opiate receptor might be partly related to the regulation of basal tone, because both tetrodotoxin and clonidine, but not naloxone, were reported to inhibit resting endogenous acetylcholine overflow in the guinea-pig colon (Marino et al 1994). These antagonists and agonists had no effects on the basal tone of the duodenum, jejunum, ileum and rectum (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…This potentiation suggests that SNS‐evoked responses were caused by the activation of junctional receptors. Other studies have also used this line of reasoning to identify innervated receptors (Marino, Marcoli, de Ponti, Cosentino, Lecchini & Frigo, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an exogenously applied muscarinic agonist such as oxotremorine can aect NA release by activating inhibitory muscarinic receptors on adrenergic terminals. It has been shown that endogenous NA tonically inhibits acetylcholine release from enteric neurones (Marcoli et al, 1985;Marino et al, 1994). Facilitation of NA release by endogenous acetylcholine could thus represent an additional feedback mechanism for the modulation of neurotransmitter release from enteric cholinergic neurones.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat stomach and jejunum, EP 3 prostanoid receptors (Racke et al, 1995) and interleukin-1 receptors (Hurst & Collins, 1993), respectively, have been reported. In the guinea-pig colon, we have recently provided evidence in favour of an a 2 -adrenoceptor-mediated feedback autoinhibition (Marino et al, 1994) as well as of the functional relevance of m and k opioid receptors (Marino et al, 1993;Cosentino et al, 1995a) and of glutamatergic receptors of the N-methyl-D-aspartate subtype (Cosentino et al, 1995b) in the modulation of NA release.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation